Coercion and Its Discontents: The Promise and Peril of Increasingly Restrictive of Vaccination Mandates; Comment on "Convergence on Coercion: Functional and Political Pressures as Drivers of Global Childhood Vaccine Mandates" - James Colgrove (Kerman University of Medical Sciences, 2023)
Attwell and Hannah present a cogent analysis of why policy-makers in four jurisdictions chose to use coercive approaches to increase vaccination rates between 2015 and 2017. Their study calls attention to the challenging political calculations that are necessary when choosing between coercion and persuasion to increase vaccine uptake. Further research is needed on the consequences of making a mandatory vaccination policy more restrictive, in order to better understand the backlash and resistance such a strategy may provoke. Although one reason that policy-makers may choose a coercive approach is that it is cheaper and easier to implement than a persuasive one, sociopolitical trends and backlash related to the COVID-19 pandemic may make coercive policies more politically risky in the coming years.